Crystalline and amorphous polymeric solid nitrogen: Low-Temperature Thermodynamics and Structure - Yakub, L.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The structure and thermodynamic functions of solid high-density nonmolecular nitrogen in the crystalline and amorphous phases are studied by a Monte Carlo simulation technique on the basis of the potential model proposed earlier for the cubic gauche polymeric crystal. The solid amorphous state was created by fast melting followed by instant quenching of the crystalline structure. The computed atom-atom distribution functions in such solids are characteristic for amorphous structure. The simulation also reveals the negativity of thermal expansion coefficient of amorphous solid at high density and low temperatures, as was previously found to be the case in the cubic gauche nonmolecular nitrogen crystal. Analysis of the force model shows specific anharmonicity characteristics of the crystalline vibrations responsible for this effect.